Method for producing metal member, metal member, and metal-resin composite

By performing two roughening treatments on the surface of the metal substrate, a surface structure of micron and nanometers is formed, which solves the problem of insufficient bonding strength between metal members and resin members in the prior art, and achieves excellent bonding strength and airtightness.

CN119800358APending Publication Date: 2025-04-11MITSUI CHEMICALS INC +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311312775.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to provide a metal member and a metal resin composite having excellent bonding strength with a resin member.

Method used

The surface of the substrate containing metal was roughened twice: the first step was to roughen the etching solution containing amine compounds, nitrogen-containing heteroaromatic compounds, hydrogen peroxide and inorganic acid, and the second step was to perform further roughening treatment using an alkaline solution to form a micron- and nano-scale surface structure.

Benefits of technology

Excellent bonding strength with resin members is achieved, and the airtightness and overall performance of the metal resin composite are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004488381300000011
    Figure HDA0004488381300000011
  • Figure HDA0004488381300000012
    Figure HDA0004488381300000012
  • Figure HDA0004488381300000013
    Figure HDA0004488381300000013
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a metal member, a metal member, and a metal-resin composite. A method for manufacturing a metal member, the method including a step for roughening the surface of a substrate containing a metal, the roughening including a step in which the following treatments are performed in this order: a first roughening treatment performed using an etching solution containing an amine compound, a nitrogen-containing heteroaromatic compound, hydrogen peroxide, and an inorganic acid, and a second roughening treatment performed using an etching solution containing an amine compound, a nitrogen-containing heteroaromatic compound, hydrogen peroxide, and an inorganic acid; and a second roughening treatment using an alkaline solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing a metal component, a metal component, and a metal-resin composite. Background Art

[0002] Metal-resin composites have both properties derived from metal components (electrical conductivity, thermal conductivity, etc.) and properties derived from resin components (insulation, etc.), and have been used in many applications such as vehicle structural parts. In the production of metal-resin composites, metal components with roughened surfaces are sometimes used in order to improve the bonding strength with resin components. Such metal components are described in, for example, Patent Document 1.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 6387543 Summary of the invention

[0006] Problems to be solved by the invention

[0007] An object of one embodiment of the present disclosure is to provide a method for manufacturing a metal member having excellent bonding strength with a resin member, a metal member having excellent bonding strength with a resin member, and a metal-resin composite having excellent bonding strength with a resin member.

[0008] Means for solving problems

[0009] The present disclosure includes the following aspects.

[0010] <1> A method for manufacturing a metal component, comprising the step of roughening the surface of a substrate comprising metal,

[0011] The roughening treatment includes the steps of sequentially performing the following treatments: a first roughening treatment using an etching solution containing an amine compound, a nitrogen-containing heteroaromatic compound, hydrogen peroxide, and an inorganic acid; and a second roughening treatment using an alkaline solution.

[0012] <2> The method for manufacturing a metal component according to claim 1, wherein the second roughening treatment sequentially comprises:

[0013] Stage 1 using an alkaline solution comprising permanganate; and

[0014] Stage 2 is carried out using an alkaline solution containing chlorite.

[0015] <3> like <1> or <2> In the method for manufacturing a metal component, the content of the amine compound in the etching solution is 0.0001 mass % to 5 mass % relative to the total mass of the etching solution.

[0016] <4> like <1> ~ <3> The method for producing a metal member according to any one of the preceding claims, wherein the content of the nitrogen-containing heteroaromatic compound in the etching solution is 0.01% by mass to 2.0% by mass based on the total mass of the etching solution.

[0017] <5> like <1> ~ <4> The method for manufacturing a metal member according to any one of the preceding claims, wherein the content of hydrogen peroxide in the etching solution is 0.5% by mass to 7% by mass based on the total mass of the etching solution.

[0018] <6> like <1> ~ <5> The method for producing a metal member according to any one of the preceding claims, wherein the content of the inorganic acid in the etching solution is 5% by mass to 20% by mass based on the total mass of the etching solution.

[0019] <7> like <1> ~ <6> The method for producing a metal member according to any one of the preceding claims, wherein the amine compound is an amino acid compound.

[0020] <8> like <7> The method for manufacturing a metal component, wherein the amino acid compound is an aliphatic amino acid or a salt thereof.

[0021] <9> like <7> The method for manufacturing a metal component, wherein the amino acid compound is an α-amino acid or a salt thereof.

[0022] <10> like <1> ~ <9> The method for producing a metal member according to any one of the preceding claims, wherein the nitrogen-containing heteroaromatic compound is an azole compound.

[0023] <11> like <10> In the method for manufacturing a metal component, the azole compound is a triazole compound.

[0024] <12> like <1> ~ <11> The method for manufacturing a metal member according to any one of the preceding claims, wherein the substrate includes at least one of copper and a copper alloy.

[0025] <13> A metal component comprising copper or a copper alloy,

[0026] The metal component has a surface with a roughness index of 10.0 or more, wherein the roughness index is a ratio of the real surface area (m2) measured by the krypton adsorption method to the surface area (m2) measured by the krypton adsorption method. 2 ) divided by the geometric surface area (m 2 ) is obtained.

[0027] <14> A metal-resin composite comprising:

[0028] <13> the metal component; and

[0029] A resin member joined to the aforementioned metal member.

[0030] Effects of the Invention

[0031] According to one embodiment of the present disclosure, a method for manufacturing a metal member having excellent bonding strength with a resin member, a metal member having excellent bonding strength with a resin member, and a metal-resin composite having excellent bonding strength with a resin member can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] [ Figure 1A ] is a SEM image of a cross section of the metal-resin composite produced in Example 1.

[0033] [ Figure 1B ] is a SEM image of a cross section of the metal-resin composite produced in Example 1.

[0034] [ Figure 1C ] is a SEM image of a cross section of the metal-resin composite produced in Comparative Example 1.

[0035] [ Figure 2 ] is a diagram schematically showing a test piece for airtightness evaluation.

[0036] [ Figure 3 ] is a cross-sectional view schematically showing a diagonal cross section of the test piece for airtightness evaluation. DETAILED DESCRIPTION

[0037] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the minimum value and the maximum value, respectively.

[0038] In the numerical ranges described stepwise in the present disclosure, the upper limit or lower limit described in a certain numerical range may be replaced by the upper limit or lower limit of another numerical range described stepwise, or may be replaced by a value shown in the Examples.

[0039] In the present disclosure, when there are multiple substances belonging to each component in the material, the amount of each component in the material refers to the total amount of the multiple substances present in the material unless otherwise specified.

[0040] In the present disclosure, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0041] <Method for manufacturing metal member>

[0042] The method for manufacturing a metal component of the present disclosure is a method for manufacturing a metal component, comprising the steps of roughening the surface of a substrate including metal,

[0043] The roughening treatment includes the steps of sequentially performing the following treatments: a first roughening treatment using an etching solution containing an amine compound, a nitrogen-containing heteroaromatic compound, hydrogen peroxide, and an inorganic acid; and a second roughening treatment using an alkaline solution.

[0044] In the method of the present disclosure, the roughening treatment performed on the surface of the metal substrate includes a first roughening treatment using an etching solution containing an amine compound, a nitrogen-containing heteroaromatic compound, hydrogen peroxide and an inorganic acid, and a second roughening treatment using an alkaline solution.

[0045] By making the roughening treatment include two kinds of roughening treatments, it is possible to achieve excellent bonding strength for the resin component. The reason for this is that, for example, a micrometer-level concave-convex structure is formed on the surface of the substrate by the first roughening treatment, and then a nanometer-level fine structure (hereinafter also referred to as a nanostructure) is imparted to the surface of the substrate by the second roughening treatment.

[0046] Hereinafter, the first roughening treatment and the second roughening treatment will be described.

[0047] (First Roughening Treatment)

[0048] In the first roughening treatment, an etching solution containing an amine compound, a nitrogen-containing heteroaromatic compound, hydrogen peroxide, and an inorganic acid is brought into contact with the surface of a substrate containing a metal.

[0049] The method of bringing the etching liquid into contact with the substrate is not particularly limited, and examples thereof include an immersion method of immersing the substrate in the etching liquid, a spray method of spraying the etching liquid onto the substrate, and a rotation method of spraying the etching liquid onto a rotating substrate.

[0050] The temperature of the etching solution can be appropriately adjusted in consideration of the material of the substrate, the composition of the etching solution, etc., and is preferably 30°C to 60°C, and more preferably 35°C to 45°C, for example.

[0051] The time of the first roughening treatment (ie, the contact time between the metal material and the etching solution) can be appropriately adjusted in consideration of the material of the substrate, the composition of the etching solution, etc., and is preferably 60 seconds to 480 seconds, and more preferably 150 seconds to 300 seconds.

[0052] The pH of the etching solution may change during the first roughening treatment. In this case, the pH of the etching solution may be adjusted as necessary.

[0053] [Amine compounds]

[0054] The amine compound contained in the etching solution functions as a complexing agent for dissolving the metal in the form of a metal complex. The amine compound is not particularly limited, and examples thereof include alkanolamine compounds, hydroxylamine compounds, and amino acid compounds.

[0055] Examples of the alkanolamine compound include monoalkanolamine compounds, dialkanolamine compounds, and trialkanolamine compounds. Examples of the monoalkanolamine compound include monoethanolamine, 2-methylaminoethanol, 2-ethylaminoethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, monopropanolamine, dimethylaminoethanol, and salts thereof. Examples of the dialkanolamine compound include diethanolamine, N-methyldiethanolamine, dibutanolamine, and salts thereof. Examples of the trialkanolamine compound include triisopropanolamine, triethanolamine, and salts thereof.

[0056] Examples of the hydroxylamines include hydroxylamine, N-methylhydroxylamine, N,N-dimethylhydroxylamine, N,N-diethylhydroxylamine, hydroxylamine sulfate, and hydroxylamine hydrochloride.

[0057] The amine compounds may be used alone or in combination of two or more.

[0058] From the viewpoint of etching properties, the content of the amine compound is preferably 0.0001% to 5% by mass, more preferably 0.01% to 0.5% by mass, further preferably 0.01% to 0.3% by mass, and particularly preferably 0.01% to 0.1% by mass, relative to the total mass of the etching solution.

[0059] From the viewpoint of more easily suppressing leakage of the fluid, the amine compound is preferably an amino acid compound.

[0060] The amino acid compound functions as a complexing agent for dissolving the metal in the form of a metal complex, and can suitably perform the above function because of its high adsorption capacity for metals.

[0061] In addition, the amino acid compound can reduce the effect of the concentration of hydrogen peroxide as an oxidant on the etching rate. Specifically, since hydrogen peroxide decomposes over time, the concentration of hydrogen peroxide in the etching solution sometimes decreases, thereby reducing the etching rate. In contrast, by using the amino acid compound, the effect of the reduction in etching rate due to the decomposition of hydrogen peroxide can be reduced.

[0062] Furthermore, the amino acid compound has a pH buffering effect and can suppress the pH fluctuation of the etching solution to stabilize the pH.

[0063] In the present disclosure, "amino acid compound" refers to amino acids and salts thereof. Amino acids are organic compounds having two functional groups, amino group and carboxyl group.

[0064] The amino acid compound is not particularly limited, and examples thereof include alanine, glutamic acid, glycine, leucine, isoleucine, proline, serine, threonine, valine, β-alanine, γ-alanine, arginine, asparagine, aspartic acid, cysteine, glutamine, histidine, lysine, methionine, tryptophan, tyrosine, ornithine, phenylalanine, 4-chlorophenylalanine, 4-bromophenylalanine, 4-nitrophenylalanine, 3-(3,4-dihydrophenyl)alanine, α-methylphenylalanine, and salts thereof. Examples of the above salts include alkali metal salts and ammonium salts.

[0065] From the viewpoint of etching properties, the amino acid compound is preferably an aliphatic amino acid or a salt thereof.

[0066] From the viewpoint of etching properties, the amino acid compound is preferably an α-amino acid or a salt thereof.

[0067] The amino acid compound may be used alone or in combination of two or more.

[0068] From the viewpoint of etching properties, the content of the amino acid compound is preferably 0.0001% to 5% by mass, more preferably 0.01% to 0.5% by mass, further preferably 0.01% to 0.3% by mass, and particularly preferably 0.01% to 0.1% by mass, relative to the total mass of the etching solution.

[0069] [Nitrogen-containing heteroaromatic compounds]

[0070] The nitrogen-containing aromatic heterocyclic compound contained in the etching solution suppresses rapid etching of the metal, thereby suitably contributing to the adjustment of the roughening of the metal surface.

[0071] In the present disclosure, a "nitrogen-containing aromatic heterocyclic compound" refers to a compound having a heterocyclic ring containing nitrogen.

[0072] The nitrogen-containing aromatic heterocyclic compounds are not particularly limited and examples thereof include: 5-membered ring compounds such as pyrrole compounds, pyrazole compounds, imidazole compounds, triazole compounds, and their derivatives; 6-membered ring compounds such as pyridine compounds, pyridazine compounds, pyrazine compounds, pyrimidine compounds, triazine compounds, and their derivatives; heterocyclic compounds such as indole, purine, quinoline, isoquinoline, quinoxaline, cinnoline, quinazoline, phthalazine, naphthyridine, pteridine, acridine, naphthazine, phenazine, phenanthroline, and their derivatives.

[0073] From the viewpoint of etching properties, the nitrogen-containing heteroaromatic compound is preferably an azole compound.

[0074] The azole compound is not particularly limited, and examples thereof include triazole compounds such as 1,2,3-triazole, 1,2,4-triazole, 5-phenyl-1,2,4-triazole, 5-amino-1,2,4-triazole, 1H-benzotriazole, 1-methyl-benzotriazole, 5-methyl-1H-benzotriazole, and 3-amino-1H-triazole; tetrazoles such as 1H-tetrazole, 5-methyl-1H-tetrazole, 5-phenyl-1H-tetrazole, and 5-amino-1H-tetrazole; imidazoles such as 1H-imidazole and 1H-benzimidazole; thiazoles such as 1,3-thiazole and 4-methylthiazole, and the like.

[0075] From the viewpoint of etching properties, the azole compound is preferably a triazole compound.

[0076] The nitrogen-containing heteroaromatic compound may be used alone or in combination of two or more.

[0077] From the viewpoint of easily ensuring bonding strength and airtightness, the content of the nitrogen-containing heteroaromatic compound is preferably 0.01 to 2.0% by mass, and more preferably 0.8 to 1.5% by mass, based on the total mass of the etching solution.

[0078] [Hydrogen peroxide]

[0079] The hydrogen peroxide contained in the etching solution functions as an oxidizing agent for oxidizing the metal.

[0080] From the viewpoint of etching properties, the content of hydrogen peroxide is preferably 0.5% by mass to 7% by mass, and more preferably 1.3% by mass to 3.0% by mass, relative to the total mass of the etching solution.

[0081] [Inorganic acid]

[0082] The inorganic acid contained in the etching solution is used to dissolve the oxidized metal.

[0083] Inorganic acid is not particularly limited, and for example sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, hypophosphorous acid, carbonic acid, sulfamic acid, boric acid, hydrofluoric acid etc. can be enumerated. When considering environmental load, preferably use inorganic acid other than hydrochloric acid, phosphoric acid and hydrofluoric acid. In addition, from the viewpoint that the dissolution rate of copper is fast and also excellent in economic aspect, preferably use sulfuric acid.

[0084] The inorganic acid may be used alone or in combination of two or more.

[0085] From the viewpoint of etching properties, the content of the inorganic acid is preferably 5 to 20% by mass, more preferably 5 to 15% by mass, further preferably 6 to 13% by mass, and particularly preferably 8 to 12% by mass, based on the total mass of the etching solution.

[0086] [Other ingredients]

[0087] The etching solution may contain water in addition to the amino acid compound, the nitrogen-containing heteroaromatic compound, hydrogen peroxide, and the inorganic acid. The water is preferably water obtained by removing impurities such as metal ions and organic matter, particulate particles, etc. by distillation, ion exchange treatment, filter treatment, various adsorption treatments, etc. Pure water and ultrapure water are particularly preferred.

[0088] In order to make deeper bumps and depressions, the etching solution may contain a halide ion source that generates fluoride ions, chloride ions, bromide ions, etc. As halide ions, chloride ions are generally preferred. Examples of halide ion sources include alkali metal salts such as sodium chloride, ammonium chloride, and potassium chloride, oxohalides such as sodium chlorate and potassium chlorate, and copper chloride.

[0089] The halide ion sources may be used alone or in combination of two or more.

[0090] When a halide ion source is contained, the content of the halide ion source may be about 0.0001 mass % to 0.05 mass % based on the total mass of the etching solution from the viewpoint of etching properties.

[0091] In order to adjust the etching properties, the etching solution may contain a water-soluble organic solvent such as alcohol, glycol, or ether as a solvent other than water.

[0092] The water-soluble organic solvent may be used alone or in combination of two or more.

[0093] When the etching solution contains a water-soluble organic solvent, the content of the water-soluble organic solvent may be about 0.1% by mass to 20% by mass based on the total mass of the etching solution from the viewpoint of etching properties.

[0094] In order to adjust the etching properties, the etching solution may contain an organic acid other than the amino acid compound. Examples of the organic acid other than the amino acid compound include aliphatic carboxylic acids and aromatic carboxylic acids.

[0095] The above-mentioned organic acids may be used alone or in combination of two or more.

[0096] When the etching solution contains an organic acid, the content of the organic acid may be about 1% by mass to 15% by mass based on the total mass of the etching solution from the viewpoint of etching properties.

[0097] In addition to the above-mentioned components, the etching solution may also contain various additives commonly used in etching solutions. Examples of additives include stabilizers, solubilizers, defoamers, pH adjusters, specific gravity adjusters, viscosity modifiers, wettability improvers, chelating agents, oxidants, reducing agents, surfactants, etc. The additives may be used alone or in combination of two or more.

[0098] When the etching solution contains an additive, the content of the additive may be approximately 0.001% by mass to 10% by mass relative to the total mass of the etching solution.

[0099] [pH]

[0100] From the viewpoint of etching properties, the pH of the etching solution at 25° C. is preferably 3.0 or less, and more preferably 1.0 or less. The pH is measured using a pH meter.

[0101] (Second roughening treatment)

[0102] In the second roughening treatment, an alkaline solution is brought into contact with the substrate.

[0103] The method of bringing the alkaline solution into contact with the substrate is not particularly limited, and examples thereof include an immersion method of immersing the substrate in the alkaline solution, a spray method of spraying the alkaline solution onto the substrate, and a rotation method of spraying the alkaline solution onto a rotating substrate.

[0104] From the viewpoint of effectively forming a nanostructure on the surface of the substrate after the first roughening treatment, in the second roughening treatment, it is preferred that an alkaline solution containing an oxidant is brought into contact with the substrate. The oxidant is preferably a permanganate, more preferably potassium permanganate or sodium permanganate, and further preferably potassium permanganate.

[0105] A preferred embodiment of the second roughening treatment includes a treatment including a first step using an alkaline solution containing permanganate and a second step using an alkaline solution containing chlorite in this order.

[0106] [Phase 1]

[0107] In stage 1, an alkaline solution containing permanganate is brought into contact with the substrate.

[0108] In the present disclosure, the alkaline solution containing permanganate refers to a liquid containing at least permanganate and water and exhibiting alkalinity. Examples of permanganate include potassium permanganate, sodium permanganate, etc., and potassium permanganate is preferred.

[0109] By bringing an alkaline solution containing permanganate into contact with a substrate, base points for forming a nanostructure are generated on the surface of the substrate.

[0110] From the viewpoint of efficiently generating base points of the nanostructure on the surface of the substrate, the content of the permanganate is preferably 0.1 to 15% by mass, more preferably 0.5 to 10% by mass, and further preferably 1 to 5% by mass, relative to the total mass of the alkaline solution.

[0111] The pH of the alkaline solution containing permanganate is preferably 9 or higher, more preferably 11 or higher, and further preferably 13 or higher.

[0112] The alkaline solution containing permanganate may contain a component for adjusting the pH of the solution. Examples of the component for adjusting the pH of the solution include strong alkaline components such as potassium hydroxide and sodium hydroxide, and potassium hydroxide is preferred.

[0113] The content of the component for adjusting pH can be selected from the range of, for example, 0.1% by mass to 15% by mass with respect to the total mass of the alkaline solution.

[0114] The water contained in the alkaline solution containing permanganate is preferably pure water, and more preferably ultrapure water.

[0115] The alkaline solution containing permanganate may contain various additives in addition to the above-mentioned components. Examples of the additives include the additives exemplified as the additives that may be contained in the above-mentioned etching solution.

[0116] When the alkaline solution containing permanganate contains an additive, the content of the additive may be approximately 0.001% by mass to 10% by mass based on the total mass of the alkaline solution.

[0117] The temperature of the alkaline solution when carrying out the first step is, for example, preferably 40°C to 80°C, and more preferably 50°C to 70°C.

[0118] The time of the first stage (that is, the contact time with the alkaline solution) is, for example, preferably 60 seconds to 600 seconds, and more preferably 180 seconds to 480 seconds.

[0119] [Phase 2]

[0120] In stage 2, an alkaline solution containing chlorite is contacted with the substrate.

[0121] In the present disclosure, the alkaline solution containing chlorite refers to a liquid containing at least chlorite and water and exhibiting alkalinity. Examples of chlorite include sodium chlorite and potassium chlorite, and sodium chlorite is preferred.

[0122] By bringing the alkaline solution containing permanganate into contact with the substrate, a nanostructure composed of a metal oxide grows from base points generated by bringing the alkaline solution containing permanganate into contact with the substrate.

[0123] From the viewpoint of efficiently growing the nanostructure, the content of chlorite is preferably 0.1% to 15% by mass, more preferably 1% to 10% by mass, and even more preferably 2% to 7% by mass, relative to the total mass of the alkaline solution.

[0124] The pH of the alkaline solution containing chlorite is preferably 9 or higher, more preferably 11 or higher, and further preferably 13 or higher.

[0125] The alkaline solution containing chlorite may contain a component for adjusting the pH of the solution. Examples of the component for adjusting the pH of the solution include strong alkaline components such as potassium hydroxide and sodium hydroxide, and sodium hydroxide is preferred.

[0126] The content of the component for adjusting pH can be selected from the range of, for example, 0.1% by mass to 15% by mass with respect to the total mass of the alkaline solution.

[0127] The water contained in the alkaline solution containing chlorite is preferably pure water, and more preferably ultrapure water.

[0128] The alkaline solution containing chlorite may contain various additives in addition to the above-mentioned components. Examples of the additives include the additives exemplified as the additives that may be contained in the above-mentioned etching solution.

[0129] When the alkaline solution containing chlorite contains an additive, the content of the additive may be approximately 0.001% by mass to 10% by mass based on the total mass of the alkaline solution.

[0130] The temperature of the alkaline solution when carrying out the second step is, for example, preferably 40°C to 80°C, and more preferably 50°C to 70°C.

[0131] The time of the second stage (that is, the contact time of the metal material and the alkaline solution) is, for example, preferably 60 seconds to 600 seconds, and more preferably 180 seconds to 480 seconds.

[0132] [Pre-treatment process]

[0133] The method for manufacturing a metal member may include a pre-treatment step before the roughening step.

[0134] In the pretreatment step, for example, a treatment is performed to make the surface of the substrate into a state suitable for roughening treatment.

[0135] Specific examples of pretreatment include treatments for removing oxide films and films formed by hydroxides, etc., present on the surface of the substrate (for example, mechanical polishing, chemical polishing, etc.), and treatments for removing dirt such as engine oil present on the surface of the substrate (for example, a degreasing process using an alkaline solution, etc.).

[0136] [Post-processing process]

[0137] The method for manufacturing a metal member may include a post-processing step after the roughening step.

[0138] In the post-treatment process, for example, the substrate after the roughening treatment is cleaned.

[0139] Specific examples of post-treatment include washing with water and ultrasonic washing for removing dirt.

[0140] The type of metal contained in the metal component manufactured by the method of the present disclosure is not particularly limited. Specifically, the metal includes aluminum, iron, copper, nickel, gold, silver, platinum, cobalt, zinc, lead, tin, zirconium, titanium, niobium, chromium, aluminum, magnesium, manganese, alloys containing the above metals, and plated materials formed by plating the base materials of the above metals and alloys.

[0141] Examples of the alloy include brass, phosphor bronze, steel (e.g., stainless steel), brass products ("shin brass" in Japanese), etc. In addition, examples of the plated material (i.e., a material formed by plating a base material of the metal or alloy include plated steel, and examples of the material of the plated layer include zinc, nickel, chromium, etc.

[0142] Among the metals listed above, the metal member preferably includes at least one of copper and a copper alloy.

[0143] The shape of the metal member is not particularly limited, and examples thereof include flat plates, disks, curved plates, rods, cylinders, blocks, etc. The shape of the surface of the metal member is not particularly limited, and examples thereof include flat surfaces and curved surfaces.

[0144] When the metal component is plate-shaped, its thickness is not particularly limited, and can be, for example, 1 mm to 20 mm. For example, the thickness of the metal component used for cooling units, bus bars, etc. can be 1 mm to 5 mm, and the thickness of the metal component used for cooling parts for vehicles can be 1 mm to 5 mm.

[0145] <Metallic components>

[0146] The metal component of the present disclosure comprises copper or a copper alloy.

[0147] The metal component has a surface with a roughness index of 10.0 or more, wherein the roughness index is a ratio of the real surface area (m2) measured by the krypton adsorption method to the surface area (m2) measured by the krypton adsorption method. 2 ) divided by the geometric surface area (m 2 ) is obtained.

[0148] In the following, the real surface area (m2 ) divided by the geometric surface area (m 2 ) is also called the “roughness index”.

[0149] The metal component of the present disclosure has a surface with a roughness index of 10.0 or more. That is, a fine concavo-convex structure is formed on the surface of the metal component. Moreover, by allowing the resin component to enter the concavo-convex structure of the metal component, the anchoring effect is fully presented, and a strong bond can be obtained. As a result, the interface between the metal component and the resin component has high airtightness and shows excellent bonding strength.

[0150] In addition, the metal member of the present disclosure includes copper or a copper alloy. A metal member including copper or a copper alloy and having a surface with a roughness index of 10.0 or more has not been reported before.

[0151] From the viewpoint of improving the bonding strength between the metal member and the resin member, the roughness index is preferably 15.0 or more, more preferably 17.0 or more, and even more preferably 20.0 or more.

[0152] The upper limit of the roughness index is not particularly limited, but may be 150.0 or less, 125.0 or less, or 100.0 or less from the viewpoint of making it easy for the resin member to penetrate into the concavo-convex structure of the metal member.

[0153] In the present disclosure, the geometric surface area of ​​a metal component is a value obtained from the dimensions of the object to be measured. For example, when the object to be measured is a rectangular parallelepiped with a length of X, a width of Y, and a height of Z, the geometric surface area S is obtained as S=2XY+2YZ+2ZX.

[0154] In the present disclosure, the real surface area of ​​the metal member can be obtained by subtracting the specific surface area (m 2 The specific surface area of ​​the object to be measured was determined by multiplying the mass (g) of the object to be measured by the method described in the Examples.

[0155] The metal component of the present disclosure may be a metal component manufactured using the above-mentioned method for manufacturing the metal component of the present disclosure.

[0156] <Metal-resin composite>

[0157] The metal-resin composite according to the present disclosure includes: the metal member according to the present disclosure; and a resin member bonded to at least a portion of a surface of the metal member.

[0158] The portion of the surface of the metal member to which the resin member is bonded is preferably the roughened surface of the metal member described above.

[0159] [Resin components]

[0160] The resin contained in the resin component is not particularly limited and can be selected according to the purpose of the metal component. As the resin, for example, polyolefin resin (for example, polypropylene), polyvinyl chloride, polyvinylidene chloride, polystyrene resin, AS resin, ABS resin, polyester resin (for example, polybutylene terephthalate), poly (methyl) acrylic resin, polyvinyl alcohol, polycarbonate resin, polyamide resin, polyimide resin, polyether resin, polyacetal resin, fluorine resin, polysulfone resin, polyphenylene sulfide resin, polyketone resin and other thermoplastic resins (including elastomers), and phenolic resin, melamine resin, urea resin, polyurethane resin, epoxy resin, unsaturated polyester resin and other thermosetting resins can be cited. These resins can be used alone or in combination of two or more.

[0161] From the viewpoint of moldability, the resin contained in the resin member is preferably a thermoplastic resin.

[0162] The resin contained in the resin member may contain various compounding agents, such as fillers, heat stabilizers, antioxidants, pigments, weathering agents, flame retardants, plasticizers, dispersants, lubricants, mold release agents, antistatic agents, and the like.

[0163] The resin member may contain a filler. Examples of the filler include glass fiber, carbon fiber, carbon particles, clay, talc, silica, minerals, cellulose fiber, etc. These fillers may be used alone or in combination of two or more.

[0164] [constitute]

[0165] The structure of the metal-resin composite is not particularly limited as long as it includes a metal member and a resin member bonded to at least a portion of the surface of the metal member, and may be appropriately designed in consideration of the use of the metal-resin composite.

[0166] The metal-resin composite may include, for example, a plurality of metal members, or may include one metal member or two or more metal members including different metals.

[0167] The metal-resin composite may include, for example, a plurality of resin members, or may include one type of resin member or two or more types of resin members containing different resins.

[0168] Metal-resin composites can be used for various purposes. Examples of the use of metal-resin composites include cooling units, bus bars, cooling parts for vehicles, structural parts for vehicles, vehicle-mounted products, housings of electronic devices, housings of home appliances, building components, structural parts, machine parts, various automotive parts, parts for electronic devices, home-oriented uses such as furniture and kitchen products, medical equipment, parts for building materials, other structural parts, and exterior parts.

[0169] (Method for producing metal-resin composite)

[0170] The metal-resin composite according to the present disclosure is not particularly limited in its production method, but can be suitably produced by the method for producing a metal-resin composite according to the present disclosure described below.

[0171] The method for manufacturing a metal-resin composite according to the present disclosure comprises the following steps:

[0172] a step of placing the metal member according to the present disclosure in a mold (hereinafter sometimes referred to as a "mold placing step"); and

[0173] A step of supplying a molten or softened resin to a mold (hereinafter, sometimes referred to as a "resin supply step").

[0174] In the mold placement step, the metal member is placed in the mold, and in the resin supply step, the molten or softened resin is supplied to the mold.

[0175] The molten resin supplied to the mold is solidified in a state of being in contact with at least a portion of the roughened surface of the metal member, thereby forming the resin member.

[0176] The details and preferred embodiments of the resin are the same as the details and preferred embodiments of the resin contained in the resin member contained in the above-mentioned metal-resin composite.

[0177] Other manufacturing conditions may be appropriately selected according to known conditions.

[0178] [Example]

[0179] Hereinafter, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to these examples.

[0180] <Example 1>

[0181] A copper alloy plate (thickness: 2 mm) with an alloy number of C1100 specified in JIS H3100:2012 was cut into pieces having a length of 45 mm and a width of 18 mm to prepare test pieces for producing metal members.

[0182] [Pre-treatment process]

[0183] The test piece was immersed in a 2.6 mass % sodium hydroxide aqueous solution (55° C.) containing 0.16 mass % sodium gluconate for 5 minutes while being ultrasonically cleaned, and then washed with water (20 seconds×3 times) to perform a degreasing step.

[0184] Next, the metal material was immersed in a 0.002 mass % sodium hydroxide aqueous solution (35° C.) containing 0.1 mass % benzotriazole and 0.3 mass % 2-isopropoxyethanol for 20 seconds, and then washed with water (20 seconds×3 times) to remove the film on the surface of the test piece.

[0185] [First Roughening Step]

[0186] 9.5 mass % sulfuric acid, 2 mass % hydrogen peroxide, 1.1 mass % benzotriazole, 0.024 mass % glycine, and 0.00225 mass % sodium chloride were dissolved in water to prepare an etching solution. The test piece was immersed in the etching solution (40°C) for 3 minutes and then washed with water (20 seconds × 3 times) to form a concave-convex structure on the surface of the test piece. The pH of the etching solution at 25°C was measured using a pH meter "D-71" manufactured by Horiba, Ltd., and the result was 0.3.

[0187] [Second roughening process: first stage]

[0188] 2 mass % of potassium permanganate as permanganate and 3 mass % of potassium hydroxide were dissolved in water to prepare an alkaline solution. The pH of the alkaline solution was 13.3.

[0189] The test piece after the first roughening step was immersed in the alkaline solution (60° C.) for 3.5 minutes and then washed with water (20 seconds×3 times).

[0190] [Second roughening process: second stage]

[0191] 5 mass % of sodium chlorite as chlorite and 10 mass % of sodium hydroxide were dissolved in water to prepare an alkaline solution. The pH of the alkaline solution was 13.9.

[0192] The test piece after the second step was immersed in the alkaline solution (60° C.) for 3.5 minutes and then washed with water (20 seconds×3 times).

[0193] [Post-processing process]

[0194] The test piece was immersed in water (normal temperature) for 3 minutes while ultrasonic cleaning was performed to remove dirt. Then, the test piece was dried at 80° C. for 20 minutes. In the above manner, the metal member of Example 1 was produced.

[0195] <Comparative Example 1>

[0196] A metal member of Comparative Example 1 was produced by the same method as in Example 1 except that the second roughening step was not performed.

[0197] [Measurement of roughness index]

[0198] The specific surface areas of the metal members produced in Example 1 and Comparative Example 1 were measured by the following method, and the roughness index of the roughened surface was calculated from the measurement results. As a result, the roughness index of the metal member of Example 1 was 21.4, and the roughness index of the metal member of Comparative Example 1 was 8.6.

[0199] (Determination of specific surface area)

[0200] After the metal component was degassed by vacuum heating (100°C), the adsorption isotherm was measured by krypton gas adsorption method at liquid nitrogen temperature (77K) using BELSORP-max (manufactured by Microtrac BEL Co., Ltd.), and the specific surface area of ​​the metal component was calculated by the BET method.

[0201] [Measurement of bonding strength (1)]

[0202] The metal components produced in Example 1 and Comparative Example 1 were set in a small dumbbell metal insert mold installed in an injection molding machine J55-AD manufactured by Nippon Steel Works. Then, polypropylene (PP) was injection molded in the mold to produce a metal-resin composite having a resin layer formed on the metal component. The area of ​​the interface between the metal component and the resin layer was 10 mm×50 mm. The shear bonding strength (MPa) of the metal-resin composite was measured by a method in accordance with ISO19095-2.

[0203] Specifically, a dedicated chuck was attached to a tensile tester "Model 1323 (manufactured by Aikoh Engineering Co., Ltd.)" and the breaking load (N) was measured at room temperature (23°C) under the conditions of a chuck distance of 60 mm and a tensile speed of 10 mm / min.

[0204] The measured breaking load (N) is divided by the area of ​​the interface between the metal member and the resin layer (50 mm 2 ), and the shear bond strength (MPa) was obtained.

[0205] As a result, the shear bonding strength of Example 1 was 28 MPa, and the shear bonding strength of Comparative Example 1 was 20 MPa.

[0206] [Measurement of bonding strength (2)]

[0207] A metal-resin composite was prepared in the same manner as in the measurement of bonding strength (1), except that the resin used in injection molding was changed to polyphenylene sulfide (PPS). The metal-resin composite was subjected to a four-point bending test in accordance with ISO 19095-2 to measure the bending strength (MPa).

[0208] As a result, the bending strength of Example 1 was 68.3 MPa, and the bending strength of Comparative Example 1 was 50.1 MPa.

[0209] [Cross-sectional observation of metal components]

[0210] Figure 1A and Figure 1B 2 shows a SEM image of a cross section of the metal-resin composite (resin layer: PP) prepared in Example 1.

[0211] Figure 1C 2 shows a SEM image of a cross section of the metal-resin composite (resin layer: PP) prepared in Comparative Example 1.

[0212] The metal members of Example 1 and Comparative Example 1 subjected to the first roughening treatment both had micrometer-order concavo-convex structures formed on their surfaces due to the corrosive action of the etching solution.

[0213] In the metal member of Example 1 which was subjected to the second roughening treatment after the first roughening treatment, a nanostructure composed of copper oxide was further formed on the surface in a state where the micron-order concavo-convex structure was formed.

[0214] [Evaluation of airtightness]

[0215] In order to evaluate the airtightness of the metal-resin composite (resin layer: PP), a helium leak test using a helium leak detector was performed. As the helium leak detector, M-212LD manufactured by Canon Anelva Technix Corporation was used. Figure 2 The shape of the test piece for airtightness evaluation specified in ISO19095-2 (Type D.2.2 specimen) is shown in FIG. Figure 3 The cross-sectional shape in the diagonal direction is shown in FIG. For this test piece, a light absorbing member was injected into a rectangular metal flat plate (50 mm×50 mm×2 mm) with a hole having a diameter of 20 mm, thereby bonding a resin member (see FIG. Figure 3 ). It should be noted that in order to ensure the airtightness of the O-ring (gasket) provided in the gap between the helium leak detector test fixture (test port flange surface) and the test piece, an area not subjected to roughening treatment was provided on the peripheral edge of the metal surface of the test piece.

[0216] In Example 1 and Comparative Example 1, 10 test pieces were prepared respectively, and a helium leakage test was carried out.

[0217] Specifically, the helium leakage of the test piece (specifically, the helium leakage within 1 minute after pressurization) and the blank sample (4.5×10 -7 Pa·m 3 / second) compared with the leakage rate increase within 10%.

[0218] As a result, in Example 1, helium leakage was not confirmed in 10 out of 10 test pieces, and in Comparative Example 1, helium leakage was not confirmed in 7 out of 10 test pieces.

Claims

1. A method for manufacturing a metal component, comprising the step of roughening the surface of a substrate comprising metal, The roughening process comprises the following steps: A first roughening treatment using an etching solution containing an amine compound, a nitrogen-containing heteroaromatic compound, hydrogen peroxide, and an inorganic acid; and The second roughening treatment is performed using an alkaline solution.

2. The method for manufacturing a metal member according to claim 1, wherein: The second roughening process includes: Stage 1 using an alkaline solution comprising permanganate; and Stage 2 is carried out using an alkaline solution containing chlorite.

3. The method for manufacturing a metal member according to claim 1, wherein: The content of the amine compound in the etching solution is 0.0001% by mass to 5% by mass based on the total mass of the etching solution.

4. The method for manufacturing a metal member according to claim 1, wherein: The content of the nitrogen-containing heteroaromatic compound in the etching solution is 0.01 mass % to 2.0 mass % relative to the total mass of the etching solution.

5. The method for manufacturing a metal member according to claim 1, wherein: The content of hydrogen peroxide in the etching solution is 0.5 mass % to 7 mass % relative to the total mass of the etching solution.

6. The method for manufacturing a metal member according to claim 1, wherein: The content of the inorganic acid in the etching solution is 5% by mass to 20% by mass based on the total mass of the etching solution.

7. The method for manufacturing a metal member according to claim 1, wherein: The amine compound is an amino acid compound.

8. The method for manufacturing a metal member according to claim 7, wherein: The amino acid compound is an aliphatic amino acid or a salt thereof.

9. The method for manufacturing a metal member according to claim 7, wherein: The amino acid compound is an α-amino acid or a salt thereof.

10. The method for manufacturing a metal member according to claim 1, wherein: The nitrogen-containing heteroaromatic compound is an azole compound.

11. The method for manufacturing a metal member according to claim 10, wherein: The azole compound is a triazole compound.

12. The method for manufacturing a metal member according to any one of claims 1 to 11, wherein: The substrate includes at least one of copper and a copper alloy.

13. A metal component comprising copper or a copper alloy, The metal component has a surface with a roughness index of 10.0 or more, wherein the roughness index is a ratio of the real surface area (m2) measured by the krypton adsorption method to the surface area (m2) measured by the krypton adsorption method. 2 ) divided by the geometric surface area (m 2 ) is obtained.

14. A metal-resin composite comprising: The metal member according to claim 13; and A resin member joined to the metal member.

Citation Information

Patent Citations

  • Change-over of operation mode for air conditioner

    JP1988087543A